Increased Focus on Employee Holistic Wellbeing: A Bibliometric Analysis - Judijanto, Loso; Andiani, Paramita; Novitasari, Salwa Aulia (Westscience Press, 2025)
This study conducts a bibliometric analysis to map the intellectual structure, thematic development, and global research trends surrounding employee holistic wellbeing. Drawing data from the Scopus database and analyzing 2000–2024 publications using VOSviewer, the study reveals four major thematic clusters: psychological stress and health, organizational engagement and satisfaction, performance-driven wellbeing strategies, and sustainability-linked ethical frameworks. The temporal overlay shows a transition from deficit-oriented topics like job stress and burnout toward emerging themes such as remote work, mindfulness, and resilience. Author co-citation networks identify Schaufeli W.B. and Bakker A.B. as foundational scholars, with contributions from interdisciplinary domains including psychology, HRM, and organizational behavior. Geographic analysis highlights dominant research from the United States, United Kingdom, and Australia, with growing participation from India, China, and Malaysia. The study concludes by emphasizing the need for integrated, cross-cultural, and proactive approaches to employee wellbeing in research and practice.